Practicality of Study Program Profile Booklet as a Promotional Tool in the Mathematics Education Study Program: English - Palupi, Dini; Rahmadeni, Fevi; Margaretha, Delvi Sari; Fadilah, Dwi Miftah; Alfendra, Jyordi; Wanti, Meta Putri Rahma; Khasanah, Ulfa (International Journal of Education Research and Development, 2025)
This research aims to develop promotional media for the IAIN Curup Tadris Mathematics study program based on booklets. The booklet contains information that the bidder of goods or services wishes to convey in promoting the superiority of the goods/services being offered and consists of approximately 30 pages. The booklet development model used is the 4D model (Define, Design, Develop, and Disseminate). The research results showed that the booklet developed met the valid criteria with an average score of 3.7. The results of the student response questionnaire regarding the practicality of the Booklet showed that the average attractiveness aspect was 4.193 (good), the average convenience aspect was 3.813 (good), the average usefulness aspect was 3.68 (good). The overall average result was 3.895 in the Practical category.